Adaptive spatiotemporal distribution of soil microfungi in 'Evolution Canyon' III, Nahal Shaharut, extreme southern Negev Desert, Israel - GRISHKAN, ISABELLA; BEHARAV, ALEX; KIRZHNER, VALERY; NEVO, EVIATAR (Biological journal of the Linnean Society, 2007)
We examined adaptive spatiotemporal mycobiota structure in the soil of 'Evolution Canyon' III, Nahal Shaharut, in the extreme southern Negev, Israel. A total of 223 species representing 80 genera were isolated using the soil dilution plate method. The microfungal communities in all localities and seasons were characterized by a superdominance of dark-coloured species with large multicelled conidia: Ulocladium atrum, U. botrytis, Alternaria alternata, and Al. chlamydospora. Species of the genus Aspergillus (mainly As. fumigatus) and teleomorphic ascomycetes comprised a basic part of the thermotolerant mycobiota obtained at a temperature of 37 °C. Isolate density displayed high positive dependence on organic matter content. Density was subject to drastic spatiotemporal (especially spatial) fluctuations, with maximum levels found in the shady valley bottom locality. The lowest biodiversity indices were estimated in localities under shrubs and in the most stressful summer and spring. The results demonstrated a clear effect of harsh desert climatic and edaphic selection on the adaptive variation of the mycobiota studied.